ALGORITHMS FOR SEPARATING THE QRS COMPLEX FROM ECG (Web of Teachers: Inderscience Research, 2025)
ECG is a diagnostic signal recorded in a patient's body at standard electrode positions, and it reflects the electrical activity of the heart muscle. One of the main features of the ECG is the form of an impulse wave, also called the QRS complex. This coincides with the time of depolarization of the complex ventricles and has an important diagnostic value.